APPLICATION OF SIX SIGMA METHOD EVALUATING THE QUALITY OF PERIPHERAL BLOOD CELL TESTING AT PHUONG CHAU INTERNATIONAL HOSPITAL - Thanh Tri, Vo; Thuy An, Bui; Trung Tin, Le; Phuoc Loi, Le; Thi Bao Ha, Nguyen (Journal of Health and Aging, 2025)
The Six Sigma approach enables laboratories to objectively evaluate analytical performance, refine IQC protocols, and establish suitable IQC frequencies. This study aimed to evaluate the quality and optimize the IQC procedure for selected hematology tests on the Advia 2120i automated hematology analyzer. A cross-sectional descriptive study was conducted using internal quality control and external quality assessment data from April 2024 to December 2024 at Phuong Chau International Hospital. The results showed that WBC and PLT achieved sigma values >4 at all three IQC levels. HGB had sigma values ranging from 3 to
Keywords: sigma metrics; total allowable error; bias; coefficient of variation